THE ROLE OF VERBS, TYPES OF VERBS AS WELL AS LEXICAL, MORPHOLOGICAL, AND SYNTACTIC CHARACTERISTICS OF VERBS IN ENGLISH LANGUAGE - Zubaydova Nilufar Ne’matullayevna; Haqberdieva Gulrux; Kasimova Saodat Mirsaidovna; Hakimov Halim Nasimovich; Toliboyev Bekzod Furkatzoda (International Journal on Orange Technologies, 2020)
Given article, there are fully information about verbs, several types as well as kinds of verb with examples. Besides that, in article reader can find beneficial information about the morphological, and syntactic characteristics of verbs in English text